AN ANALYSIS OPTIMIZATION OF PASTRY PRODUCT PRODUCTION - Ailsa Azalia; Tanto Pratondo Utomo; Tirza Hanum (Politeknik Negeri Lampung, 2022)
Pastry industry in Bandar Lampung are well developed and like other industry they have goal to achieve many profit with minimal cost. This research aim to analyze the production process which already applied and give advice on improvements to the production process of pastry products to get the maximum profit. All data were analyzed by LINDO (Linear Interactive Discrete Optimizer) progam. The results of this research on optimal conditions obtained the maximum profit was Rp. 88.237.000,00 per month. The resources with an overload status which have not beenmaximum utilized were raw materials, production employes working hours, dough sheeter machine working hours and oven machine working hours. The mixer machine working hours was the only one resource which had limited use to working.